ANALISIS D.HORTON, TEORI KAPASITAS ORGANISASI BADAN NARKOTIKA NASIONAL KABUPATEN SOLOK (PROGRAM PENCEGAHAN DAN PEMBERDAYAAN MASYARAKAT/P2M) - AULIA, ULFA; Sasmita, Siska; Khaidir, Afriva; Mubarak, Adil (Jurnal Teori dan Riset Administrasi Publik, 2024)
This research was motivated by a number of problems faced by the Prevention and Community Empowerment Division (P2M) of The National Narcotics Boards of Solok Regency (BNNK) in carrying out their work programs. Even though there was an increase in the nominal value of the organization's budget (AD/ART), the allocation for P2M activities actually decreased. Likewise, the numbers of both instructors and activity implementers are insufficient.This has an impact on decreasing P2M activities while at the same time the distribution and use of drugs is increasingly widespread in this area. This research aims to find out what organizational capacity the P2M Division of BNNK Solok has in carrying out its work program. This study employs a qualitative method with a descriptive approach. Research informants were selected using purposive sampling techniques. The types of data collected are primary and secondary data. By referring to the Organizational Capacity Theory proposed by Horton, namely: human resources; infrastructure, technology and financial resources; strategic leadership; program and process management; networks of cooperation and relationships with other parties, it is found that only the strategic leadership dimension is adequate. Meanwhile, other dimensions: human resources; infrastructure, technology, and financial resources; process dimensions and process management; and the collaborative networks and relationships with other parties are inadequate to support the P2M Program at BNNK Solok.